The Impact of Work Experience and Compensation on Employee Performance in a Growing Company - Nurliana Sirait, Friska; Purwadi, Anto; Rusdi, Rusdi (International Journal of Management Science and Information Technology, 2025)
This study examines the relationship between work experience, compensation, and employee performance in growing companies. Using a quantitative approach and survey design, the research involved 100 technology, retail, and manufacturing employees. Data was collected through a questionnaire covering work experience, compensation, and employee performance. Descriptive analysis results show that most respondents have work experience relevant to their current job and are satisfied with the compensation received. However, there is variation in productivity and work quality. This study tests the simultaneous influence of work experience and compensation on employee performance through multiple linear regression analysis. The regression results indicate that work experience has a more significant impact on employee performance than compensation. Additionally, normality and multicollinearity tests confirm that the data meets the necessary assumptions for regression analysis. The findings clearly show the factors influencing employee performance in growing companies. Company management may consider enhancing compensation and offering more experience-based training to support improved employee performance.